The Relationship of Stress Level with The Fair Production of Breast Milk on Nurses Who are Breastfeeding at Panti Waluyo Hospital Malang - Susmini Susmini (STIKes Patria Husada Blitar, 2022)
The nursing profession has an important role in providing health services in every health institution. Demands for professional services provide a workload that can increase stress on nurses, one of which can have an impact on breast milk production for nursing mothers. This study aims to determine the relationship between stress levels and the smooth production of breast milk in nursing nurses at Panti Waluya Hospital, Malang. This type of research is pre-experimmental with a cross sectional approach. The research sample used a simple random sampling technique with a total sample of 44 respondents. The research was conducted at Panti Waluya Hospital. Most of the 28 respondents (63.7%) had moderate stress levels, most of the respondents (61.3%) had non-fluent milk production. Based on the results of the Chi Square test, p-value + (0.036)<(0.05) is obtained so that Ho is rejected, meaning that there is a relationship between stress levels and the smooth production of breast milk for nurses at Panti Waluya Hospital, Malang. Nurses are expected to increase milk production by using stress coping and increasing nutritional intake.